Positive electrode materials, positive electrode sheets, and batteries

CN122992056APending Publication Date: 2026-10-27SHENZHEN HIGHPOWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611467703.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,这一策略本质上仅从表面或局部修饰入手,并未触及钴酸锂本征结构的天花板,其局限性在高电压场景下尤为凸显:首先,包覆层通常离子电导率较低,过量添加反而增大界面阻抗,牺牲倍率性能;其次,常规掺杂难以在维持层状结构稳定性的同时兼顾高锂含量,导致可逆容量大幅折损;再者,单一改性手段缺乏对“应力-化学”耦合失效机制的协同调控,高压循环中晶格内部的各向异性形变无法有效释放,进一步加速结构崩塌

Benefits of technology

[0015]本申请提供的技术方案可以包括以下有益效果:本申请构建了“骨架支撑相-间隙填充相-多功能活性相”三级功能分置协同结构,通过将三种专属功能颗粒之间形成的深度结构互补与性能协同,从而有效破解了电池在容量、压实密度、能量密度及循环稳定性之间难以兼顾的技术矛盾。在这一协同体系中,三种颗粒在物理空间与电化学功能上实现了高度耦合:在物理空间层面,大粒径的R-3m相骨架颗粒、小粒径的R-3m相填充颗粒以及中等粒径的P63mc相活性颗粒,通过粒径级配,在极片内部构建了极致的三级紧密堆积结构。这种物理上的协同不仅显著提升了颗粒堆积的密实度和极片的压实密度,还通过优化颗粒接触网络,大幅降低了界面阻抗,为电荷传输提供了高效通路。在电化学性能层面,R-3m相颗粒构建的稳固力学骨架,有效保障了极片的结构稳定性与抗辊压开裂能力;而嵌入其中的P63mc相颗粒,则凭借其本征的宽锂离子传输通道与优异的高压晶体结构稳定性,在承担高容量增益的同时,有效抑制了高电压工况下的结构坍塌与相变畸变。三种颗粒各司其职又紧密配合,在物理堆积与电化学功能上形成了协同效应,最终在保障极片力学稳定与高压实密度的同时,实现了高电压下电池容量与循环稳定性的有效提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992056A_ABST
    Figure CN122992056A_ABST
Patent Text Reader

Abstract

This application relates to a cathode material, a cathode sheet, and a battery. The cathode material comprises a first lithium cobalt oxide, a second lithium cobalt oxide, and a third lithium cobalt oxide; the first and second lithium cobalt oxides have an R-3m crystal structure; the third lithium cobalt oxide has a P63mc crystal structure; the cathode material satisfies the following relationship: A > C > B; wherein the particle size D50 of the first lithium cobalt oxide is A μm; the particle size D50 of the second lithium cobalt oxide is B μm; and the particle size D50 of the third lithium cobalt oxide is C μm. The cathode material provided in this application enables the cathode sheet to have a high compaction density, while effectively improving the battery's capacity and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to cathode materials, cathode sheets and batteries. Background Technology

[0002] Lithium cobalt oxide (LiCoO2) has long held a dominant position as the cathode material for lithium-ion batteries in consumer electronics due to its high tap density, excellent volumetric energy density, and mature and stable preparation process.

[0003] Currently, commercially available lithium cobalt oxide generally adopts a layered structure with the R-3m space group. However, under high voltage conditions of 4.5V and above, this intrinsic structure faces severe challenges: on the one hand, the capacity improvement is no longer sufficient to meet the ever-increasing energy density requirements, and the physical morphology and chemical properties of the cathode particles themselves also limit further breakthroughs in compaction density; on the other hand, the layered framework is prone to irreversible transformation into spinel or rock salt phases, leading to a sharp deterioration in cycle performance. To alleviate this contradiction, the industry often adopts modification strategies such as surface coating or bulk doping to suppress interfacial side reactions and lattice distortion by constructing physical barriers or introducing heterovalent ions. However, this strategy essentially only addresses the surface or localized modifications and does not address the inherent structural limitations of lithium cobalt oxide. Its limitations are particularly pronounced in high-voltage scenarios: First, the coating layer typically has low ionic conductivity, and excessive addition can increase interfacial impedance, sacrificing rate performance. Second, conventional doping struggles to maintain layered structural stability while ensuring high lithium content, leading to a significant reduction in reversible capacity. Furthermore, single modification methods lack synergistic control over the stress-chemical coupling failure mechanism, preventing the effective release of anisotropic deformation within the lattice during high-voltage cycling, further accelerating structural collapse. Therefore, relying solely on traditional surface or bulk modifications cannot reconcile the fundamental contradiction between high specific capacity and high-voltage cycling stability, while also offering very limited improvement in compaction density.

[0004] Therefore, there is an urgent need to develop a new type of cathode material to simultaneously achieve a synergistic improvement in high capacity, high actual density, and long cycle life. Summary of the Invention

[0005] To address or partially address the problems existing in related technologies, this application provides a positive electrode material, a positive electrode sheet, and a battery. The positive electrode material enables the positive electrode sheet to have a high compaction density, while effectively improving the battery's capacity and cycle stability.

[0006] The first aspect of this application provides a cathode material, wherein the cathode material includes a first lithium cobalt oxide, a second lithium cobalt oxide, and a third lithium cobalt oxide; The first lithium cobalt oxide and the second lithium cobalt oxide have an R-3m crystal structure; The third lithium cobalt oxide has a P63mc crystal structure; The cathode material satisfies the following relationship: A > C > B; Wherein, the particle size D50 of the first lithium cobalt oxide is A μm; the particle size D50 of the second lithium cobalt oxide is B μm; and the particle size D50 of the third lithium cobalt oxide is C μm. The first lithium cobalt oxide has the chemical formula LiCo. 1-f M f O2, wherein M includes at least two of W, Nb, Al, Mg, Ti, La, Y, Zr, and Sr, and 0.004 < f < 0.05; The chemical formula of the second lithium cobalt oxide is LiCo. 1-h N h O2, wherein N includes at least two of B, Y, Al, W, Ti, Mg, Mn, Ni, La, Zr, Nb, and Sr, and 0.005 < h < 0.06; The third lithium cobalt oxide is modified with at least one element selected from Ni, Mn, and Al, and the content of the modifying element is 0.005 mol% to 5 mol%. The mass ratio of the first lithium cobalt oxide, the second lithium cobalt oxide, and the third lithium cobalt oxide is (5~9.3):(0.5~3):(0.2~2).

[0007] The cathode material as described in the first aspect, wherein 15 ≤ A ≤ 22; And / or, 3≤B≤7; And / or, 6≤C≤10.

[0008] The cathode material as described in the first aspect, wherein the cathode material satisfies the following relationship: 1.0≤a1≤1.8; And / or, 1.0 ≤ a2 ≤ 1.9; And / or, 1.0 ≤ a3 ≤ 4.2; Wherein, the aspect ratio of the first lithium cobalt oxide particle is a1; the aspect ratio of the second lithium cobalt oxide particle is a2; and the aspect ratio of the third lithium cobalt oxide particle is a3.

[0009] As described in the first aspect, the cathode material, wherein 0.55 ≤ a2 / a1 ≤ 1.95; And / or, 0.25≤a2 / a3≤2.98.

[0010] As described in the first aspect, the cathode material has a particle size distribution D50 / (D10+D90) of 2.05~2.85. And / or, the particle size distribution D50 / (D10+D90) of the second lithium cobalt oxide is 2.20~2.95; And / or, the particle size distribution D50 / (D10+D90) of the third lithium cobalt oxide is 0.9~3.6.

[0011] As described in the first aspect, in the cathode material, the third lithium cobalt oxide has the chemical formula LiCo. 1-x-y- z Ni x Mn y Al z O2, where 0.002≤x≤0.03, 0.003≤y≤0.02, and 0.002≤z≤0.03.

[0012] The cathode material as described in the first aspect, wherein the X-ray diffraction pattern of the cathode material has characteristic diffraction peaks at 2θ of 19.0°±0.2° and 18.7°±0.2°, respectively; And / or, the compaction density of the positive electrode material is 4.1 g / cm³. 3 ~5.0g / cm 3 ; And / or, the compaction density of the positive electrode sheet including the positive electrode material is 4.2 g / cm³. 3 ~5.1g / cm 3 .

[0013] A second aspect of this application provides a positive electrode sheet, wherein the positive electrode material is as described in the first aspect.

[0014] A third aspect of this application provides a battery, wherein a positive electrode plate is included as described in the second aspect.

[0015] The technical solution provided in this application can include the following beneficial effects: This application constructs a three-level functionally separated and synergistic structure of "skeleton support phase - interstitial filling phase - multifunctional active phase". By complementing the deep structure and synergizing the performance of the three dedicated functional particles, it effectively solves the technical contradiction of the battery's difficulty in balancing capacity, compaction density, energy density, and cycle stability. In this synergistic system, the three particles achieve a high degree of coupling in terms of physical space and electrochemical function: at the physical space level, the large-diameter R-3m phase skeleton particles, the small-diameter R-3m phase filling particles, and the medium-diameter P63mc phase active particles, through particle size gradation, construct an extremely compact three-level packing structure inside the electrode. This physical synergy not only significantly improves the density of particle packing and the compaction density of the electrode, but also greatly reduces the interfacial impedance by optimizing the particle contact network, providing an efficient pathway for charge transport. At the electrochemical performance level, the robust mechanical framework constructed by the R-3m phase particles effectively ensures the structural stability and resistance to rolling cracking of the electrode. Meanwhile, the embedded P63mc phase particles, with their inherently wide lithium-ion transport channels and excellent high-voltage crystal structure stability, effectively suppress structural collapse and phase transition distortion under high-voltage conditions while achieving high capacity gain. These three types of particles, each performing its specific function while working closely together, create a synergistic effect in both physical stacking and electrochemical function. Ultimately, this ensures the mechanical stability and high solid density of the electrode while effectively improving battery capacity and cycle stability under high voltage.

[0016] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit this application. Attached Figure Description

[0017] Figure 1 The images show the XRD patterns of the positive electrode sheets of Example 1 and Comparative Example 1.

[0018] Figure 2 This is a SEM image of the positive electrode sheet of Example 1.

[0019] Figure 3 The first-week charge-discharge diagrams are for the batteries of Example 1 and Comparative Example 1.

[0020] Figure 4 The diagram shows the cycle specific capacity of the batteries in Example 1 and Comparative Example 1 at 45°C. Detailed Implementation

[0021] To facilitate understanding of this application, it will be described in detail below. However, before describing this application in detail, it should be understood that this application is not limited to the specific embodiments described. It should also be understood that the terminology used herein is for the purpose of describing specific embodiments only and is not intended to be restrictive.

[0022] Where a numerical range is provided, it should be understood that every intermediate value between the upper and lower limits of the range and any other specified or intermediate value within the specified range is covered within this application. The upper and lower limits of these smaller ranges may be independently included in the smaller range and are also covered within this application, subject to any explicitly excluded limits within the specified range. Where the specified range includes one or two limits, the range excluding any or both of those included limits is also included within this application.

[0023] Unless otherwise defined, all terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. While the methods and materials described herein, or any equivalent methods and materials, may also be used in the implementation or testing of this application, preferred methods and materials are now described.

[0024] Currently, commercially available lithium cobalt oxide generally adopts a layered structure with the R-3m space group. However, under high voltage conditions of 4.5V and above, this intrinsic structure faces severe challenges: on the one hand, the capacity improvement is no longer sufficient to meet the ever-increasing energy density requirements, and the physical morphology and chemical properties of the cathode particles themselves also limit further breakthroughs in compaction density; on the other hand, the layered framework is prone to irreversible transformation into spinel or rock salt phases, leading to a sharp deterioration in cycle performance. To alleviate this contradiction, the industry often adopts modification strategies such as surface coating or bulk doping to suppress interfacial side reactions and lattice distortion by constructing physical barriers or introducing heterovalent ions. However, this strategy essentially only addresses the surface or localized modifications and does not address the inherent structural limitations of lithium cobalt oxide. Its limitations are particularly pronounced in high-voltage scenarios: First, the coating layer typically has low ionic conductivity, and excessive addition can increase interfacial impedance, sacrificing rate performance. Second, conventional doping struggles to maintain layered structural stability while ensuring high lithium content, leading to a significant reduction in reversible capacity. Furthermore, single modification methods lack synergistic control over the stress-chemical coupling failure mechanism, preventing the effective release of anisotropic deformation within the lattice during high-voltage cycling, further accelerating structural collapse. Therefore, relying solely on traditional surface or bulk modifications cannot reconcile the fundamental contradiction between high specific capacity and high-voltage cycling stability, while also offering very limited improvement in compaction density.

[0025] To address the aforementioned issues, this application provides a cathode material comprising a first lithium cobalt oxide, a second lithium cobalt oxide, and a third lithium cobalt oxide; the first and second lithium cobalt oxides have an R-3m crystal structure; and the third lithium cobalt oxide has a P63mc crystal structure.

[0026] The cathode material of this application satisfies the following relationship: A > C > B; wherein, the particle size D50 of the first lithium cobalt oxide is A μm; the particle size D50 of the second lithium cobalt oxide is B μm; and the particle size D50 of the third lithium cobalt oxide is C μm.

[0027] The cathode material of this application adopts a composite structure design of "bicrystalline + three-dimensional particle size", specifically including a first lithium cobalt oxide, a second lithium cobalt oxide, and a third lithium cobalt oxide. Among them, the first lithium cobalt oxide and the second lithium cobalt oxide both belong to the traditional R-3m crystal structure, but they complement each other in terms of particle size: the first lithium cobalt oxide is a large-diameter particle, and the second lithium cobalt oxide is a small-diameter particle; while the third lithium cobalt oxide adopts a P63mc crystal structure with a wider lithium-ion transport channel and higher structural stability, and its particle size is limited to between the first lithium cobalt oxide and the second lithium cobalt oxide.

[0028] The first lithium cobalt oxide with an R-3m crystal structure serves as a mechanical framework unit, capable of constructing the mechanical framework and main channels of the conductive network of the electrode. This large particle size not only ensures the overall structural mechanical stability of the electrode and endows it with excellent resistance to rolling cracking, but also provides a physical basis for high packing density for the overall system while providing basic capacity.

[0029] The second lithium cobalt oxide with an R-3m crystal structure exists as an "interstitial filling phase" that fills and conducts bridging units; its small particle size allows it to precisely fill the tiny gaps between the first lithium cobalt oxides, significantly increasing the particle contact network by bringing the particles closer together, thereby providing local conductive pathways and stress buffering.

[0030] The third lithium cobalt oxide, with its P63mc crystal structure, serves as the core "multifunctional active phase" of the entire composite system, undertaking the dual functions of capacity enhancement and structural stability. On the one hand, the P63mc space group possesses a wider lithium-ion transport channel, which can further improve the specific capacity of the battery. Its embedding in the three-gradient system can overcome the bottleneck of traditional multi-gradient systems failing to significantly improve capacity from an intrinsic material perspective, thereby greatly increasing the battery's energy density. On the other hand, this phase inherently possesses excellent high-voltage crystal structure stability. Under high-voltage operating conditions, its layered structure collapse and phase transition distortion during high-voltage lithium insertion / extraction are lower, effectively improving the battery's high-voltage cycle performance. Furthermore, its uniform particle size allows it to fill some of the voids in the first and second lithium cobalt oxides, forming a functional complement and structural synergy with the framework support phase and interstitial filling phase.

[0031] This application constructs a three-tiered functional synergistic structure consisting of a "skeleton support phase, interstitial filling phase, and multifunctional active phase." By complementing the deep structures and synergizing the performance of the three types of dedicated functional particles, it effectively resolves the technical contradiction of balancing capacity, compaction density, energy density, and cycle stability in batteries. In this synergistic system, the three types of particles achieve a high degree of coupling in terms of physical space and electrochemical function: at the physical space level, large-diameter R-3m phase skeleton particles, small-diameter R-3m phase filling particles, and medium-diameter P63mc phase active particles, through particle size gradation, construct an extremely compact three-tiered packing structure within the electrode. This physical synergy not only significantly improves the density of particle packing and the compaction density of the electrode but also greatly reduces interfacial impedance by optimizing the particle contact network, providing an efficient pathway for charge transport. At the electrochemical performance level, the robust mechanical framework constructed by the R-3m phase particles effectively ensures the structural stability and resistance to rolling cracking of the electrode. Meanwhile, the embedded P63mc phase particles, with their inherently wide lithium-ion transport channels and excellent high-voltage crystal structure stability, effectively suppress structural collapse and phase transition distortion under high-voltage conditions while achieving high capacity gain. These three types of particles, each performing its specific function while working closely together, create a synergistic effect in both physical stacking and electrochemical function. Ultimately, this ensures the mechanical stability and high solid density of the electrode while effectively improving battery capacity and cycle stability under high voltage.

[0032] In one specific embodiment, the first lithium cobalt oxide has the chemical formula LiCo. 1-f M f O2, wherein M includes at least two of W, Nb, Al, Mg, Ti, La, Y, Zr, and Sr, and 0.004 < f < 0.05. Introducing at least two specific metal elements into the first lithium cobalt oxide can produce a synergistic doping effect. On the one hand, it stabilizes the crystal structure through strong bonding, suppressing lattice distortion and phase transitions during high-voltage delithiation. On the other hand, it forms a stable interface protective layer on the particle surface, effectively blocking side reactions between the framework particles and the electrolyte. Simultaneously, strictly limiting the doping amount f within a certain range ensures that the doping elements can fully exert their lattice pinning and interface stabilization effects, while avoiding excessive lattice distortion, obstruction of lithium-ion diffusion channels, or a significant decrease in intrinsic capacity due to excessive doping. Therefore, it not only ensures the high structural stability and long cycle life of the first lithium cobalt oxide as a mechanical framework but also maintains its excellent conductivity and electrochemical activity.

[0033] In one specific embodiment, the second lithium cobalt oxide has the chemical formula LiCo. 1-h N hO2, wherein N includes at least two of B, Y, Al, W, Ti, Mg, Mn, Ni, La, Zr, Nb, and Sr, with 0.005 < h < 0.06. Introducing at least two specific metallic or non-metallic elements into the second lithium cobalt oxide can produce a synergistic effect. On the one hand, the high bond energy of the dopant elements enhances grain boundary bonding, suppressing microcrack propagation during compaction and cycling. On the other hand, it constructs a stable passivation layer or solid solution structure on the particle surface, effectively reducing the side reaction activity between high specific surface area small particles and the electrolyte. Simultaneously, controlling the doping amount within a certain range ensures that the dopant elements can fully occupy lattice sites while avoiding excessive lattice distortion due to excessive doping. This guarantees the filling capacity, interfacial compatibility, and ion transport capability of the second lithium cobalt oxide, further improving the electrochemical performance of the battery.

[0034] In one specific embodiment, the third lithium cobalt oxide is modified with at least one element selected from Ni, Mn, and Al, and the content of the modifying element is 0.005 mol% to 5 mol%. Introducing Ni into the third lithium cobalt oxide can effectively improve the specific capacity of the material and optimize the electronic conductivity. The introduction of Mn can enhance the mechanical strength of the crystal framework and suppress cation mixing. Al helps to stabilize the layered structure and suppress lattice anisotropic expansion under high pressure. By precisely controlling the content of the modifying element within the above range, it is sufficient to exert the synergistic effect of lattice pinning or surface coating at the microscopic level, effectively alleviating the phase transformation stress and microcrack generation of the P63mc phase during deep delithiation, while avoiding lithium layer blockage or reduction of electrochemical active sites caused by excessive doping, thereby better balancing high energy density and long cycle life.

[0035] In one specific embodiment, the mass ratio of the first lithium cobalt oxide, the second lithium cobalt oxide, and the third lithium cobalt oxide is (5~9.3):(0.5~3):(0.2~2). For example, the mass ratio of the first lithium cobalt oxide, the second lithium cobalt oxide, and the third lithium cobalt oxide can be 5:3:2, 6:3:1, 6:2:2, 7:1:2, 7:2:1, 8:1:1, 9:0.5:0.5, 9.3:0.5:0.2, etc. At this mass ratio, the first lithium cobalt oxide, serving as the framework support phase, and the second lithium cobalt oxide, serving as the interstitial filling phase, can form a better physical gradation. Through the mechanism of large particles building the framework and small particles filling the gaps, a denser packing is achieved, thus laying the physical foundation for the high compaction density of the cathode. At the same time, this ratio precisely limits the amount of third lithium cobalt oxide, serving as a multifunctional active phase, so that it can fully utilize the high capacity and high voltage stability advantages of the P63mc crystal structure, while avoiding damage to the overall dense packing structure of the framework or the imbalance of stress distribution between particles due to excessive addition. Ultimately, while ensuring the mechanical integrity of the electrode and the ultimate compaction density, a synergistic improvement in high energy density and long cycle life is achieved.

[0036] Specifically, the mass ratio of the first lithium cobalt oxide, the second lithium cobalt oxide, and the third lithium cobalt oxide in this application can be obtained by methods such as XRD Rietveld, LPSA, and micro turbine classification.

[0037] In one specific embodiment, 15 ≤ A ≤ 22, for example, A can be 15, 16, 17, 18, 19, 20, 21, 22, etc. When the particle size of the first lithium cobalt oxide is within the above range, the first lithium cobalt oxide can better construct the main support structure of the electrode, better provide the electrode with excellent resistance to rolling cracking and a high packing density foundation, and improve the overall structural stability of the electrode. At the same time, this large particle size range reserves filling space for the subsequent small-particle-size second lithium cobalt oxide and medium-particle-size third lithium cobalt oxide, thereby ensuring the high compaction density and mechanical stability of the electrode, while laying the structural foundation for the high capacity and high-pressure stability of the overall system.

[0038] Specifically, the particle size of the first lithium cobalt oxide in this application can be obtained by testing methods such as LPSA, EBSD, SEM, and TEM.

[0039] In one specific embodiment, 3≤B≤7, for example, B can be 3, 4, 5, 6, 7, etc. When the particle size of the second lithium cobalt oxide is within the above range, the second lithium cobalt oxide can be precisely embedded in the voids of the skeleton constructed by the first lithium cobalt oxide as an interstitial filling phase, thereby eliminating the loose areas in the skeleton structure, significantly improving the compaction density and mechanical integrity of the electrode, and further reducing the interfacial impedance to optimize the charge transport path. Finally, it forms a tight physical bond and functional complementarity with the large particles as the skeleton and the medium particles as the functional core, enabling the battery to achieve high compaction, low impedance, and high stability electrochemical performance.

[0040] Specifically, the particle size of the second lithium cobalt oxide in this application can be obtained by testing methods such as LPSA, EBSD, SEM, and TEM.

[0041] In one specific embodiment, 6 ≤ C ≤ 10, for example, C can be 6, 7, 8, 9, 10, etc. When the particle size of the third lithium cobalt oxide is within the above range, the third lithium cobalt oxide, with a medium particle size, plays a key bridging and gaining role in the system as a "multifunctional active phase," enabling it to further fill the secondary voids remaining between the first lithium cobalt oxide (large particles) and the second lithium cobalt oxide (small particles), thereby perfecting the "large-medium-small" three-level close-packed structure and optimizing the compaction density of the electrode. At the same time, this particle size specification allows it to be uniformly dispersed between the framework and the filling phase, playing a supporting role in physics, and electrochemically, thanks to the intrinsic high capacity and high-voltage stability of its P63mc crystal structure, it significantly improves the energy density and cycle life of the positive electrode without destroying the overall mechanical framework.

[0042] Specifically, the particle size of the third lithium cobalt oxide in this application can be obtained by testing methods such as LPSA, EBSD, SEM, and TEM.

[0043] In one specific embodiment, 1.0 ≤ a1 ≤ 1.8; wherein, the aspect ratio of the first lithium cobalt oxide particles is a1. For example, a1 can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, etc. This aspect ratio range allows the first lithium cobalt oxide to maintain a spherical shape while possessing moderate anisotropy. This morphology is beneficial for the first lithium cobalt oxide to achieve a more compact and orderly stacking through rotation and rearrangement during coating and rolling, reducing the bridging effect and porosity caused by irregular shape, thereby improving the compaction density of the electrode. It also provides a multi-point contact and interlocking support structure when constructing the mechanical skeleton, enhancing the bonding force between particles and the overall mechanical strength of the electrode, effectively suppressing cracking and rebound during rolling. At the same time, the optimized aspect ratio also helps to construct a continuous and low-torsion electronic conductive network, reducing particle contact resistance and ensuring efficient charge transport in the main channel of the skeleton, thus achieving synergistic optimization of physical packing density, structural stability, and conductivity.

[0044] In one specific embodiment, the particle size distribution (D50 / (D10+D90)) of the first lithium cobalt oxide is 2.05~2.85. For example, the particle size distribution of the first lithium cobalt oxide can be 2.05, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.85, etc. This specific particle size distribution range ensures that the large particles, which serve as the "skeleton support phase," can form a uniform contact network during stacking, avoiding the premature filling of large particle gaps by fine powder due to excessively wide particle size distribution. This ensures that the porosity of the skeleton structure is in a better state, reserving sufficient space for the subsequent filling of small particles. At the same time, this particle size distribution can effectively eliminate the risk of damage to the electrode surface by ultra-large particles, prevent coating scratches, and reduce local stress concentration caused by excessive particle size differences, thereby ensuring the tight stacking of the positive electrode material in the electrode and thus improving the cycle stability of the battery.

[0045] In one specific embodiment, 1.0 ≤ a2 ≤ 1.9; wherein, the aspect ratio of the second lithium cobalt oxide particle is a2. For example, a2 can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, etc. This aspect ratio range gives the second lithium cobalt oxide particles a moderate anisotropy. This morphological feature allows them to adjust their posture by rotating when entering the large voids of the first lithium cobalt oxide framework, enabling them to slide more smoothly into irregular corners and narrow gaps, thus achieving higher space utilization and filling density. At the same time, this spherical geometry increases the number of contact points and the contact area between particles, constructing a more stable and continuous conductive bridging network at the microscopic level, effectively reducing contact resistance. In addition, this aspect ratio also endows the second lithium cobalt oxide particles with a certain degree of flexibility and stress dispersion ability, allowing them to buffer local stress concentration during compaction and prevent damage to the framework particles caused by hard contact. Thus, while achieving high compaction density, it ensures the integrity of the electrode microstructure and the stability of electrochemical performance.

[0046] In one specific embodiment, the particle size distribution (D50 / (D10+D90)) of the second lithium cobalt oxide is 2.20~2.95, for example, the particle size distribution of the second lithium cobalt oxide can be 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 2.95, etc. This specific particle size distribution range ensures that the small particles, as the interstitial filling phase, have a high degree of uniformity in size, enabling the second lithium cobalt oxide to be uniformly and synchronously embedded in the microscopic voids of the first lithium cobalt oxide framework. This avoids the phenomenon that large particles cannot enter the gaps or small particles agglomerate due to an excessively wide particle size distribution, thereby resulting in better filling efficiency and compaction density, and thus improving the cycle performance of the battery.

[0047] In one specific embodiment, 1.0 ≤ a3 ≤ 4.2; wherein, the aspect ratio of the third lithium cobalt oxide particle is a3. For example, a3 can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, etc. This aspect ratio range allows the third lithium cobalt oxide particles to exhibit moderate anisotropy, enabling them to tightly embed themselves into irregular microscopic spaces by rotating and adjusting their orientation when filling the secondary voids left by the first and second lithium cobalt oxides, thereby optimizing the compaction density of the electrode. Simultaneously, the moderate anisotropy increases the contact area between particles, contributing to a more robust conductive network and improving charge transport efficiency. Furthermore, this optimized aspect ratio effectively mitigates the anisotropic volume expansion of the P63mc crystal structure during high-voltage lithium insertion / extraction, reducing stress concentration and microcrack formation within the third lithium cobalt oxide particles. This significantly improves the structural stability and high-voltage cycle life of the battery while ensuring physical filling density.

[0048] In one specific embodiment, the particle size distribution (D50 / (D10+D90)) of the third lithium cobalt oxide is 0.9~3.6. For example, the particle size distribution of the third lithium cobalt oxide can be 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, etc. This specific narrow particle size distribution range ensures that the medium-sized particles, which are multifunctional active phases, can be uniformly embedded in the secondary voids remaining between the first and second lithium cobalt oxides, thereby increasing the electrode compaction density. At the same time, the uniform particle size distribution ensures that the third lithium cobalt oxide particles are evenly dispersed in the electrode, so that when undertaking high capacity and high voltage stability functions, it can maintain the consistency of lithium ion insertion / extraction and volume expansion, effectively preventing local stress concentration and microcrack propagation caused by excessive particle size differences, thereby further improving energy density and long cycle life.

[0049] In one specific embodiment, 0.55 ≤ a2 / a1 ≤ 1.95, for example, a2 / a1 can be 0.55, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 1.95, etc. When a2 / a1 is within the above range, it can ensure that the second lithium cobalt oxide, as the filling phase, can be precisely matched in size to the microscopic voids formed by the first lithium cobalt oxide skeleton. This avoids the formation of a slab effect due to the particles not being able to enter the voids because the ratio is too large, and also prevents the particles from being excessively trapped in deep voids or agglomerating because the ratio is too small, further improving the filling efficiency and the compaction density of the electrode. At the same time, the optimized particle size ratio enables small particles to build a continuous and low-torsion conductive and ion transport network between the skeleton particles, effectively reducing the interfacial impedance and physically playing the role of buffering stress and stabilizing the skeleton, ultimately ensuring the improvement of the battery's cycle performance.

[0050] In one specific implementation, 0.25 ≤ a2 / a3 ≤ 2.98, for example, a2 / a3 can be 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 2.98, etc. When a2 / a3 is within the above range, it can ensure that the second lithium cobalt oxide, as the filling phase, and the third lithium cobalt oxide, as the active phase, form a reasonable size distribution. This allows them to be orderly and non-interferingly embedded in the gaps reserved in the first lithium cobalt oxide skeleton. This avoids mutual repulsion, local bridging, or uneven filling between particles caused by imbalance in the ratio, and optimizes the filling density of the microscopic space. At the same time, the optimized particle size ratio allows the second lithium cobalt oxide to uniformly coat or bridge around the third lithium cobalt oxide, physically stabilizing the dispersion state of the high-capacity P63mc phase. Thus, while ensuring that the electrode exhibits high compaction density, it achieves efficient utilization of high-capacity active material and synergistic improvement of long-cycle stability.

[0051] Specifically, a1, a2, and a3 of this application can be obtained by testing the following method: in the image of the particle powder under a scanning electron microscope at 1000x magnification, measure the maximum and minimum diameters of a single particle, calculate the ratio of the maximum to the minimum diameter of all single particles, remove the first 10% of the maximum ratios, and remove the last 10% of the minimum ratios.

[0052] The particle size distribution of the first, second, and third lithium cobalt oxides can be obtained by the following method: disperse the particulate powder in deionized water, ultrasonically disperse for 1 min, and test it using a Malvern 3000+ laser particle size analyzer. Take the average value of three tests.

[0053] In one specific embodiment, the third lithium cobalt oxide has the chemical formula LiCo. 1-x-y-z Ni x Mn y Al z O2, where 0.002≤x≤0.03, 0.003≤y≤0.02, 0.002≤z≤0.03. The selection of Ni, Mn, and Al elements in the third lithium cobalt oxide with the above chemical formula generates a synergistic effect in the microcrystalline lattice. This not only further stabilizes the crystal framework of the P63mc phase but also constructs a stable passivation interface on the particle surface, effectively blocking side reactions between the active material and the electrolyte. Simultaneously, strictly controlling the doping amount of each element within the aforementioned trace range allows for a greater utilization of the intrinsic advantages of the third lithium cobalt oxide in filling secondary voids and providing high voltage capacity, while also achieving a synergistic improvement in high energy density, high structural stability, and long cycle life.

[0054] In one specific embodiment, the X-ray diffraction pattern of the cathode material exhibits characteristic diffraction peaks at 2θ values ​​of 19.0°±0.2° and 18.7°±0.2°, respectively. The diffraction peak at 2θ=19.0°±0.2° typically corresponds to the R-3m crystal structure of lithium cobalt oxide, while the diffraction peak at 2θ=18.7°±0.2° corresponds to the P63mc crystal structure of lithium cobalt oxide. This indicates that the material system retains both the R-3m and P63mc crystal structures, thus achieving a complementary advantage between the traditional R-3m phase and the high-capacity P63mc phase in the phase composition of the cathode. This provides a solid crystallographic basis and materials science foundation for the cathode to achieve high energy density, high structural stability, and long cycle life.

[0055] In one specific embodiment, the compaction density of the cathode material is 4.1 g / cm³. 3 ~5.0g / cm 3 For example, the compaction density of the cathode material can be 4.1 g / cm³. 3 4.2g / cm 3 4.3g / cm 3 4.4g / cm 3 4.5g / cm 3 4.6g / cm 3 4.7g / cm 3 4.8g / cm 3 4.9g / cm 3 5.0g / cm 3The first, second, and third lithium cobalt oxides, through three-level gradation synergy and extreme micro-space filling, control the powder compaction density within the aforementioned range. This ensures both high volumetric energy density and the preservation of necessary microporous channels to guarantee sufficient electrolyte wetting and low-torsion lithium ion transport, thereby improving the microstructural integrity and interface stability of the electrode, and enhancing the battery's energy density and cycle performance.

[0056] Specifically, the compaction density of the cathode material can be obtained by the following method: Take 2g of cathode material (m) and place it into the compaction density tester mold (cross-sectional area S) of Yuaneng Technology, apply a pressure of 5 tons, and record the powder thickness L. The powder compaction density = m / (S) L).

[0057] In one specific embodiment, the cathode sheet comprising the cathode material has a compaction density of 4.2 g / cm³. 3 ~5.1g / cm 3 For example, the compaction density of the positive electrode can be 4.2 g / cm³. 3 4.3g / cm 3 4.4g / cm 3 4.5g / cm 3 4.6g / cm 3 4.7g / cm 3 4.8g / cm 3 4.9g / cm 3 5.0g / cm 3 5.1g / cm 3 When the electrode compaction density of the positive electrode is within the above range, the proportion of inactive space is significantly reduced, allowing more high-capacity active material to be accommodated per unit volume, thereby improving the energy density of the battery.

[0058] Specifically, the compaction density of the positive electrode sheet can be tested using the following method: Measure the weight m1 and thickness p1 of the 12mm diameter positive electrode sheet after rolling, and then weigh the weight m2 and thickness p2 of the 12mm diameter blank aluminum foil. The compaction density of the electrode sheet = (m1-m2) / [π]. 0.36 (p1-p2)].

[0059] This application does not limit the preparation methods of the first lithium cobalt oxide, the second lithium cobalt oxide, and the third lithium cobalt oxide; the methods can be selected according to actual needs.

[0060] A second aspect of this application provides a positive electrode sheet having a high solid density, which can improve the specific capacity and cycle performance of the battery.

[0061] In one specific embodiment, the positive electrode sheet includes a positive current collector and a positive electrode coating applied to at least one side of the positive current collector. This application does not limit the choice of the positive current collector; it can be any known material suitable for use as a positive current collector, including aluminum, stainless steel, nickel plating, titanium, tantalum metal materials, carbon cloth, carbon paper, etc. The positive electrode coating of this application includes a positive electrode material, a conductive agent, and a binder. Both the conductive agent and the binder in the positive electrode coating of this application can be selected from conventional materials in the art.

[0062] The positive electrode sheet of this application can be prepared by the following steps: mixing the first lithium cobalt oxide, the second lithium cobalt oxide, and the third lithium cobalt oxide evenly to obtain the positive electrode material; then mixing the mixed powder with the conductive agent and the binder evenly in the solvent to obtain the positive electrode slurry; finally, uniformly coating the positive electrode slurry onto the surface of the positive electrode current collector and drying it to obtain the positive electrode sheet.

[0063] A third aspect of this application provides a battery that exhibits excellent capacity and cycle performance.

[0064] In one specific embodiment, the battery exhibits a discharge plateau of 3.75V ± 0.05V during charging and discharging. This voltage range corresponds to the specific thermodynamic equilibrium potential for lithium-ion insertion / extraction in the layered lithium cobalt oxide lattice, reflecting the highly reversible phase transition process and stable crystal structure within the material. This not only demonstrates the extremely low electrochemical polarization and excellent ion transport kinetics within the battery but also ensures that the battery can continuously and stably release high capacity within the core operating voltage range, providing crucial electrochemical assurance for high energy density output and long cycle life.

[0065] In one specific embodiment, the battery of this application includes a negative electrode sheet, which includes a negative electrode current collector and a negative electrode coating coated on at least one side of the negative electrode current collector. The negative electrode coating includes a negative electrode active material and a conductive agent. This application does not limit the selection of the negative electrode active material, and it can be selected according to actual needs. For example, natural graphite, artificial graphite, hard carbon, soft carbon, silicon-carbon composite materials, elemental silicon, and silicon-oxygen composite materials can be used as the negative electrode active material. The conductive agent in the negative electrode coating of this application can be selected from conventional materials in the art.

[0066] In one specific embodiment, the battery of this application further includes an electrolyte, which includes a lithium salt and an organic solvent. The lithium salt and organic solvent are lithium salts and organic solvents known in the art that can be used in electrolytes to improve the electrochemical performance of the battery, and can be specifically set as needed.

[0067] In one specific embodiment, the lithium-ion battery further includes a separator. The embodiments of this application do not have any particular restrictions on the material and shape of the separator, as long as it does not significantly impair the effect of this application. It may include porous sheet-like or non-woven fabric-like materials with excellent liquid retention. The materials of the resin or glass fiber separator include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyethersulfone, etc., and can be set according to needs.

[0068] In one embodiment, the battery may include an outer packaging that can be used to encapsulate the electrode assembly and electrolyte.

[0069] In one specific embodiment, the outer packaging of the battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch-type soft pack. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0070] This application does not impose any particular restrictions on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape.

[0071] This application does not impose any particular restrictions on the application fields of lithium batteries. They can be used in fields such as consumer batteries, power batteries for new energy vehicles, and energy storage batteries. They can also be liquid, gel, semi-solid, quasi-solid, or all-solid batteries.

[0072] Example 1 1. Preparation of positive electrode sheet Step 1: Preparation of the first lithium cobalt oxide: Li₂CO₃, Co₃O₄, Al₂O₃, MgO, and Y₂O₅ were mixed in a molar ratio of 1.1:1:0.008:0.001:0.001 and ball-milled for 4 hours. The mixture was then placed in an alumina crucible and heated to 450°C at 5°C / min under air atmosphere, held for 5 hours, and then further heated to 1050°C and held for 12 hours. After natural cooling, intermediate 1a was obtained. Intermediate 1a was then mixed with Al₂O₃, La₂O₃, and Y₂O₃ in a molar ratio of 1:0.001:0.001:0.0005 and ball-milled for 2 hours. The mixture was then placed in an alumina crucible and heated to 800°C at 5°C / min under air atmosphere, held for 6 hours. The resulting product was pulverized and graded to obtain the first lithium cobalt oxide. The first lithium cobalt oxide has an R-3m crystal structure and the chemical formula is LiCo. 0.9875 Al 0.009 Mg 0.001 La 0.001 Y 0.0015 O2, A is 18 μm, a1 is 1.36, and the particle size distribution of the first lithium cobalt oxide is 2.61.

[0073] Step 2: Preparation of the second lithium cobalt oxide: Li₂CO₃, Co₃O₄, Al₂O₃, MgO, Y₂O₅, and ZrO₂ were mixed in a molar ratio of 1.1:1:0.009:0.002:0.001:0.001 and ball-milled for 4 hours. The mixture was then placed in an alumina crucible and heated to 450°C at 5°C / min under air atmosphere, held for 5 hours, and then further heated to 980°C and held for 12 hours. After natural cooling, intermediate 2a was obtained. Intermediate 2a was then mixed with Al₂O₃, La₂O₃, and Y₂O₃ in a molar ratio of 1:0.002:0.001:0.0005 and ball-milled for 2 hours. The mixture was then placed in an alumina crucible and heated to 800°C at 5°C / min under air atmosphere, held for 6 hours. The resulting product was pulverized and classified to obtain the second lithium cobalt oxide. The second lithium cobalt oxide has an R-3m crystal structure and the chemical formula LiCo. 0.9835 Al 0.011 Mg 0.002 Zr 0.001 La 0.001 Y 0.0015 O2, B is 5 μm, a2 is 1.28, and the particle size distribution of the second lithium cobalt oxide is 2.53.

[0074] Step 3: Preparation of the third lithium cobalt oxide. Na₂CO₃, Co₃O₄, Al₂O₃, NiO, and MnO₂ were mixed in a molar ratio of 0.8:1:0.008:0.006:0.004 and ball-milled for 4 hours. The mixture was then sintered at 850°C for 36 hours in air to obtain intermediate 3a. Intermediate 3a was then mixed with LiOH / LiCl molten salt (molar ratio 1:1) at a molar ratio of 1:2. The mixture was exchanged in a reactor at 120°C for 20 hours. After washing and drying, intermediate 3b was obtained. Intermediate 3b was dispersed in H₂O, and 0.2% aluminum isopropoxide was added and stirred. After evaporation at 110°C with stirring, the mixture was sintered at 200°C in air for 6 hours to obtain the third lithium cobalt oxide. The third lithium cobalt oxide has a P₆₃mc crystal structure and its chemical formula is LiCo. 0.98 Ni 0.004 Mn 0.006 Al 0.01 O2, C is 7 μm, a3 is 2.07, and the particle size distribution of the third lithium cobalt oxide is 2.25.

[0075] Step 4: The first lithium cobalt oxide, the second lithium cobalt oxide, and the third lithium cobalt oxide obtained in Steps 1, 2, and 3 are physically mixed in a mass ratio of 7.6:1.9:0.5 to obtain the cathode material. Then, the cathode material is mixed with acetylene black and PVDF in a mass ratio of 94:3:3 to form a slurry. The slurry is then uniformly coated on aluminum foil and cut into cathode sheets with a diameter of 12 mm.

[0076] a2 / a1 is 0.94, and a2 / a3 is 0.62.

[0077] 2. Manufacturing of lithium-ion batteries Using lithium metal sheets as the negative electrode, Celgard 2500 as the separator, and a 1M LiPF6 EC / EMC / DMC (volume ratio 1:2:2) solution as the electrolyte, a CR2032 type button cell was assembled in an argon-filled glove box. The tested voltage range was 3V~4.63V.

[0078] The preparation methods of the batteries provided in Examples 2-35 and Comparative Example 4 are basically the same as those in Example 1. Specific parameters are shown in Tables 1-4.

[0079] Comparative Example 1 The preparation method of the battery in this comparative example is roughly the same as that in Example 1, except that there is no third lithium cobalt oxide in the positive electrode sheet, and the mass ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is 8:2.

[0080] Comparative Example 2 The preparation method of the battery in this comparative example is roughly the same as that in Example 1, except that there is no second lithium cobalt oxide in the positive electrode, and the mass ratio of the first lithium cobalt oxide to the third lithium cobalt oxide is 8:2.

[0081] Comparative Example 3 The preparation method of the battery in this comparative example is roughly the same as that in Example 1, except that the positive electrode does not contain the first lithium cobalt oxide, and the mass ratio of the second lithium cobalt oxide to the third lithium cobalt oxide is 8:2.

[0082] Table 1

[0083] Table 2

[0084] Table 3

[0085] Table 4

[0086] Test case The positive electrode sheets of Example 1 and Comparative Example 1 were characterized by XRD, such as... Figure 1 As shown, the main diffraction peaks of Example 1 are located at 2θ = 19.0° and 18.7°, indicating that the cathode material of Example 1 has composite diffraction peaks of both the hexagonal layered structure of the R-3m space group and the layered structure of the P63mc space group.

[0087] The positive electrode of Example 1 was subjected to SEM testing, and the results are as follows: Figure 2As shown, the first, second, and third lithium cobalt oxides all exhibit a predominantly spherical morphology, resulting in a highly compact particle packing of the electrode. This morphological characteristic endows the electrode with excellent particle packing density, a conclusion consistent with the test data in Table 3. Clearly, higher close packing ability and compaction density are directly related to a significant increase in battery energy density.

[0088] The batteries prepared in Example 1 and Comparative Example 1 were subjected to charge-discharge tests, and the results are as follows: Figure 3 As shown, the reversible specific capacity of Comparative Example 1 at a current density of 20 mA / g within a voltage window of 3V to 4.63V in the first week is only 207.1 mAh / g, which is much lower than the 216.4 mAh / g of Example 1. This indicates that the synergistic effect of the first lithium cobalt oxide, the second lithium cobalt oxide, and the third lithium cobalt oxide helps to improve the specific capacity of the battery.

[0089] The batteries prepared in Example 1 and Comparative Example 1 were subjected to charge-discharge cycle tests at a high temperature of 45°C and a current density of 40 mA / g. The results are as follows: Figure 4 As shown, after 50 cycles at 45°C, the capacity retention rate of Example 1 was 63.1%, while that of Comparative Example 1 was 31.8%, indicating that the synergistic effect of the first lithium cobalt oxide, the second lithium cobalt oxide, and the third lithium cobalt oxide can improve the high-temperature cycling performance of the battery.

[0090] The following performance tests were performed on the positive electrode sheets and batteries prepared in the examples and comparative examples: 1) Powder compaction density test: Take a 2g sample of mixed powder (m) and place it into the mold (cross-sectional area S) of the Yuaneng Technology compaction density tester. Apply a pressure of 5 tons and record the powder thickness L. Powder compaction density = m / (S) L).

[0091] 2) Electrode compaction density test: Measure the weight m1 and thickness p1 of the 12mm diameter positive electrode after rolling. Then weigh the 12mm diameter blank aluminum foil m2 and thickness p2. Electrode compaction density = (m1-m2) / [π 0.36 (p1-p2)].

[0092] 3) Initial discharge specific capacity: Place the battery in an environment of 25±2℃, charge it at a constant current of 0.1C (20mA / g) to the cutoff voltage of 4.63V, let it stand for 10min, and discharge it at a constant current of 0.1C to the cutoff voltage of 3V; record the total amount of electricity released during the discharge process (unit: mAh), divide it by the mass of the active material in the positive electrode (unit: g), and you will get the 0.1C initial discharge specific capacity (unit: mAh / g).

[0093] 4) 45℃ Cycle Retention Rate: The battery was charged and discharged at 45℃ at a rate of 0.2C (40mA / g) within the range of 3V~4.63V. The discharge capacity of the first cycle was measured as C1, and the discharge capacity of the 50th cycle was measured as C2. The cycle capacity retention rate of the 50th cycle was calculated as R2 = C2 / C1.

[0094] Table 5

[0095] As shown in Table 5, based on the comparison between Examples 1-35 and Comparative Examples 1-3, when the cathode material includes the first lithium cobalt oxide, the second lithium cobalt oxide, and the third lithium cobalt oxide, the three functional particles form a deep structural complementarity and performance synergy, thereby achieving a balance between battery capacity, compaction density, and cycle life.

[0096] Based on the comparison of Examples 1-35 and Comparative Example 4, it can be seen that when A > C > B, the three types of particles achieve high coupling in physical space through particle size gradation, thereby simultaneously improving the battery capacity, compaction density and cycle life.

[0097] According to the comparison of Examples 1 to 7, when the mass ratio of the first lithium cobalt oxide, the second lithium cobalt oxide, and the third lithium cobalt oxide is (5~9.3):(0.5~3):(0.2~2), the first and second lithium cobalt oxides form an optimized physical gradation, which provides a structural basis for the full utilization of the high capacity and high voltage stability advantages of the third lithium cobalt oxide, and ultimately ensures the high energy density and cycle performance of the battery.

[0098] According to the comparison of Examples 1, 8-10, when 15≤A≤22, the first lithium cobalt oxide can better improve the stability of the electrode, thereby improving the electrochemical performance of the battery.

[0099] According to the comparison of Examples 1 and 11-13, when 1.0≤a1≤1.8, the first lithium cobalt oxide has moderate anisotropy, which can improve the stability of the electrode and the ion transport efficiency, which is beneficial to improving the compaction density of the electrode and improving the capacity and cycle stability of the battery.

[0100] According to the comparison of Examples 1 and 14-15, when the particle size distribution of the first lithium cobalt oxide is 2.05-2.85, the porosity of the skeleton structure in the positive electrode can be optimized, ensuring the compaction density of the electrode and the electrochemical performance of the battery.

[0101] A comparison of Examples 1 and 17 shows that when the chemical formula of the first lithium cobalt oxide is LiCo... 1-f M fO2, wherein M includes at least two of W, Nb, Al, Mg, Ti, La, Y, Zr, and Sr, and when 0.004 < f < 0.05, the stability of the first lithium cobalt oxide is higher, further improving the stability of the electrode and the battery.

[0102] As can be seen from the comparison of Examples 1 and 18, when 3≤B≤5, the second lithium cobalt oxide can be better embedded in the gaps of the skeleton constructed by the first lithium cobalt oxide, thereby increasing the compaction density of the electrode and thus improving the battery capacity and cycle performance.

[0103] According to the comparison of Examples 1, 19-21, when 1.0≤a2≤1.9, the compaction density of the electrode can be improved to a greater extent, thereby improving the battery capacity and cycle performance.

[0104] According to the comparison of Examples 1 and 22-24, when the particle size distribution of the second lithium cobalt oxide is 2.20-2.95, the intercalation effect of the second lithium cobalt oxide is better, the compaction density of the electrode is higher, and the electrochemical performance of the battery is higher.

[0105] Based on the comparison of Examples 1 and 25, the chemical formula of the second lithium cobalt oxide is LiCo. 1-h N h O2, wherein N includes at least two of B, Y, Al, W, Ti, Mg, Mn, Ni, La, Zr, Nb, and Sr, and 0.005 < h < 0.06. The doping elements in the second lithium cobalt oxide further enhance the stability of the second lithium cobalt oxide, thereby improving the stability of the electrode and ultimately improving the electrochemical performance of the battery.

[0106] Based on the comparison of Examples 1, 26-28, it can be seen that when 6≤C≤10, the third lithium cobalt oxide can further optimize the compaction density of the electrode, resulting in better electrochemical performance of the battery.

[0107] According to the comparison of Examples 1, 29-31, when 1.0≤a3≤4.2, the anisotropy of the third lithium cobalt oxide particles is better, which can further improve the stability of the electrode and improve the structural stability and high-voltage cycle life of the battery.

[0108] According to the comparison of Examples 1, 32-34, when the particle size distribution of the third lithium cobalt oxide is 0.9-3.6, it helps to optimize the compaction density of the electrode and the capacity and cycle life of the battery.

[0109] According to the comparison of Examples 1 and 35, when the third lithium cobalt oxide is modified by at least one element among Ni, Mn and Al, and the content of the modifying element is 0.005 mol% to 5 mol%, the third lithium cobalt oxide has better conductivity and improves the battery capacity and cycle performance to a greater extent.

[0110] The various embodiments of this application have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or improvement of the technology in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.

Claims

1. A positive electrode material, characterized in that, The cathode material includes a first lithium cobalt oxide, a second lithium cobalt oxide, and a third lithium cobalt oxide; The first lithium cobalt oxide and the second lithium cobalt oxide have an R-3m crystal structure; The third lithium cobalt oxide has a P63mc crystal structure; The cathode material satisfies the following relationship: A > C > B; Wherein, the particle size D50 of the first lithium cobalt oxide is A μm; the particle size D50 of the second lithium cobalt oxide is B μm; and the particle size D50 of the third lithium cobalt oxide is C μm. The chemical formula of the first lithium cobalt oxide is LiCo. 1-f M f O2, wherein M includes at least two of W, Nb, Al, Mg, Ti, La, Y, Zr, and Sr, and 0.004 < f < 0.05; The chemical formula of the second lithium cobalt oxide is LiCo. 1-h N h O2, wherein N includes at least two of B, Y, Al, W, Ti, Mg, Mn, Ni, La, Zr, Nb, and Sr, and 0.005 < h < 0.06; The third lithium cobalt oxide is modified with at least one element selected from Ni, Mn, and Al, and the content of the modifying element is 0.005 mol% to 5 mol%. The mass ratio of the first lithium cobalt oxide, the second lithium cobalt oxide, and the third lithium cobalt oxide is (5~9.3):(0.5~3):(0.2~2).

2. The cathode material according to claim 1, characterized in that, 15≤A≤22; And / or, 3≤B≤7; And / or, 6≤C≤10.

3. The cathode material according to claim 1 or 2, characterized in that, The cathode material satisfies the following relationship: 1.0≤a1≤1.8; And / or, 1.0 ≤ a2 ≤ 1.9; And / or, 1.0 ≤ a3 ≤ 4.2; Wherein, the aspect ratio of the first lithium cobalt oxide particles is a1; the aspect ratio of the second lithium cobalt oxide particles is a2; and the aspect ratio of the third lithium cobalt oxide particles is a3.

4. The cathode material according to claim 3, characterized in that, 0.55≤a2 / a1≤1.95; And / or, 0.25≤a2 / a3≤2.

98.

5. The cathode material according to claim 1 or 2, characterized in that, The particle size distribution D50 / (D10+D90) of the first lithium cobalt oxide is 2.05~2.85; And / or, the particle size distribution D50 / (D10+D90) of the second lithium cobalt oxide is 2.20~2.95; And / or, the particle size distribution D50 / (D10+D90) of the third lithium cobalt oxide is 0.9~3.

6.

6. The cathode material according to claim 1, characterized in that, The chemical formula of the third lithium cobalt oxide is LiCo. 1-x-y-z Ni x Mn y Al z O2, where 0.002≤x≤0.03, 0.003≤y≤0.02, and 0.002≤z≤0.

03.

7. The cathode material according to claim 3, characterized in that, The X-ray diffraction pattern of the cathode material shows characteristic diffraction peaks at 2θ of 19.0°±0.2° and 18.7°±0.2°, respectively. And / or, the compaction density of the positive electrode material is 4.1 g / cm³. 3 ~5.0g / cm 3 ; And / or, the compaction density of the positive electrode sheet including the positive electrode material is 4.2 g / cm³. 3 ~5.1g / cm 3 .

8. A positive electrode plate, characterized in that, The positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 7.

9. A battery, characterized in that, Includes the positive electrode sheet as described in claim 8.